Performance Analysis of Water Heating System by Using Double Glazed Flat Plate Solar Water Heater - Putra, Andika; K, Arwizet; Fernanda, Yolli; Sari, Delima Yanti (Teknomekanik, 2021)
Nowadays, the use of solar energy is incredibly important to be increased since solar energy is renewable energy and also does not cause pollution. To harness solar energy, a solar collector device is needed to convert solar energy into heat energy. This study aimed to analyze the heat transfer in the flat plate solar collector which is used as a source of thermal energy in the water heating process for bathing. A double-glazed solar collector was used to absorb solar thermal energy and then transferred it to a water pipe. The pipe material used copper which has a very high conductivity value with an outer diameter of 15.7 mm. The plate collector used aluminium plates because they have high thermal conductivity. The dimensions of the collector frame were 150 cm long, 80 cm wide and 80 cm high. The collector frame was made of wood and covered with an insulator from coconut fibre with a thickness of 8 cm, with a tilt angle of 15˚. Based on the experimental process, the collector temperature was taken by using a thermocouple in order to heat the water which the inlet temperature in a bucket was 28˚C and the outlet water temperature during the experiment was 40˚C.